2018
DOI: 10.3390/app8112190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Types of Recycled Concrete Aggregates on Equivalent Concrete Strength and Drying Shrinkage Properties

Abstract: Residual mortar attached to recycled concrete aggregate (RCA) always leads to a decrease in Young’s modulus and an increase in the drying shrinkage of RCA concrete, mainly due to an increase of total mortar volume. To overcome this inherent problem, the modified and equivalent mortar volume (EMV) methods were proposed by researchers. Despite the comparable test results, both models are still subject to the slump loss problem. Thus, under the same W/C (water to cement ratio) ratio and slump condition, this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Similar results are presented in [24]. The studies described in [25] have shown that mixes containing 50% and 100% RCA and modified with a superplasticizer have reached the same consistency as the reference mix-therefore it is possible to control the consistency of mixes containing even large amounts of RCA.…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations
“…Similar results are presented in [24]. The studies described in [25] have shown that mixes containing 50% and 100% RCA and modified with a superplasticizer have reached the same consistency as the reference mix-therefore it is possible to control the consistency of mixes containing even large amounts of RCA.…”
Section: Introductionsupporting
confidence: 71%
“…Reduction of compressive and flexural strength and elasticity modulus was also described for HPC containing RCA after 7, 14 and 28 days [26]. Concretes containing 50% and 100% RCA have lower compressive strength compared to control concrete, however, the use of concrete from railway sleepers demolition caused an increase in strength [25]. The compressive strength of concrete containing RCA is 30% less than the reference concrete, and the compressive strength is 10% less.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Yang [8] analyzed the effect of different types of recycled concrete aggregates (RCAs) on the equivalent concrete strength and drying shrinkage properties. A total of six mixes were proportioned using the modified equivalent mortar volume (EMV) method with three RCAs.…”
Section: Long-term Behavior Of Recycled Aggregate Concretementioning
confidence: 99%